Análisis cinemático de la fases de doble apoyo y de salto, del remate por la zona 4 de los jugadores de la selección masculina de voleibol de antioquia, categoría mayores (2006)
ABSTRACT: 13 volleyball male players from Antioquia's major cathegory team were selected for being studied. Our purpose was to establish some kinematics parameters during double support jump phase. We used a Panasonic S-VHS M9000 Camera, a calibrated scalemeter and the Kinematrix program, in order to obtain images. We have found that most of them put the knees in a valgus position, which could produce some problems in the medial ligament and injuries in the external rnenisc. During elevation phase, the movement of both ankles was similar but the knees one was different. The advanced knee (right knee) produced a movement of continuous extension while the delay knee (left knee) produced a movement of a very little extension. The angle of resultant velocity at the end of the double support had a right correlation with the gravity center height (r = 0.50). The resultant of the horizontal velocity had an inverse correlation with the gravity center height (r = -0.63)